Resilience in Forage and Grazinglands. Issue 1 (1st January 2018) - Tracy, B. F.; Foster, J. L.; Butler, T. J.; Islam, M. A.; Toledo, D.; Vendramini, J. M. B.
ABSTRACT: The current reality of population growth, resource scarcity, and climate change requires resilient agroecosystems to sustain food production and protect the environment. This manuscript reflects a combined effort of speakers at the 2017 C6 Forage and Grazinglands Division Symposium, which was titled "Resiliency in Forage and Grazinglands." The symposium brought together speakers representing a diverse cross‐section of forage systems across the United States. Each speaker discussed resilience‐related topics from their specific region, including: the importance of diversity and use of complementary forages in grazing systems, how grazing and defoliation affect resilience, the importance of soil fertility and pest management, and development of decision aids to evaluate resilience in grazinglands. Several themes emerged that we propose would help improve the resilience of forage and grazingland systems: (i) identifying moderately diverse, site‐specific mixtures (grasses–legumes) for use in specific regions of the United States, (ii) greater use of complementary forage species such as C3 and C4 grasses to lengthen the grazing season and provide a buffer against weather variation, (iii) adoption of moderate defoliation intensities to help stabilize forage production and species composition, (iv) more attention to maintaining and improving soil fertility to improve the productivity of desirable forage species and reduce weed pressure, and (v) increase adoption of assessment tools to evaluate the relative "health" and potential resilience of forage‐livestock systems. An integrative management approach that combines many of these elements would help improve the resilience of forage and grazinglands to sustain high productivity under increasingly erratic and extreme weather.